THE ROLE OF EDUCATION IN SHAPING AN INCLUSIVE EDUCATIONAL ENVIRONMENT FOR ACHIEVING SUSTAINABLE PROGRESS IN THE GENDER DIMENSION - Єфімова, Ольга (SWorldJournal, 2026)
This article examines the role of education in creating an inclusive educational environment as a foundation for achieving sustainable progress in gender equality. It analyzes the mechanisms for implementing gender-sensitive practices within curricula an